Compositional characteristics and sources of DIC and DOC in seawater of the Okinawa Trough, East China Sea. (15th February 2019) - Zhang, Xianrong; Sun, Zhilei; Fan, Dejiang; Xu, Cuiling; Wang, Libo; Zhang, Xilin; Geng, Wei; Luan, Xiwu
Abstract: Seafloor hydrothermal systems and cold seeps contribute considerable amounts of dissolved carbon to ocean water. To investigate the compositional characteristics and potential sources of the dissolved carbon in the Okinawa Trough (OT), East China Sea (ECS), we measured the concentrations and distributions of dissolved inorganic carbon (DIC), dissolved organic carbon (DOC) and their 13 C stable isotopes in a full-depth water column in this area. Our results indicate that in the upper layer (water depth < 200 m), the dissolved carbon is mainly controlled by biological processes. In contrast, in the deeper layer, the concentration and isotopes are clearly influenced by seafloor hydrothermal and cold seep fluids in the OT. Based on our mass balance model estimation, cold seeps and hydrothermal fluids contribute up to 14.3% and 19.6%, respectively, of the seawater DIC. Our study shows that both of these extreme seafloor systems contribute considerable proportions of the local carbon budget. Moreover, they may also have an important impact on the extreme seafloor ecosystems therein.